2015
DOI: 10.1038/leu.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and CREBBP mutations: a relapse-linked malicious liaison in childhood high hyperdiploid acute lymphoblastic leukemia

Abstract: High hyperdiploidy defines the largest genetic entity of childhood acute lymphoblastic leukemia (ALL). Despite its relatively low recurrence risk, this subgroup generates a high proportion of relapses. The cause and origin of these relapses remains obscure. We therefore explored the mutational landscape in high hyperdiploid (HD) ALL with whole-exome (n=19) and subsequent targeted deep sequencing of 60 genes in 100 relapsing and 51 non-relapsing cases. We identified multiple clones at diagnosis that were primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
122
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 49 publications
12
122
0
2
Order By: Relevance
“…As expected, in all but one sample with mutations in JAK-STAT genes (CRLF2, IL7R, and JAK1/2), CRLF2 was rearranged. Interestingly, the CRLF2 neg DS-ALLs displayed a similar pattern of mutations that was reported for hyperdiploid ALLs (26), namely association between mutations in RAS signaling pathway and in chromatin remodeling genes, such as CREBBPs (Fig. 1).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…As expected, in all but one sample with mutations in JAK-STAT genes (CRLF2, IL7R, and JAK1/2), CRLF2 was rearranged. Interestingly, the CRLF2 neg DS-ALLs displayed a similar pattern of mutations that was reported for hyperdiploid ALLs (26), namely association between mutations in RAS signaling pathway and in chromatin remodeling genes, such as CREBBPs (Fig. 1).…”
Section: Resultsmentioning
confidence: 71%
“…CRLF2 neg DS-ALLs are characterized by enhanced RAS signaling coupled by mutations in chromatin remodeling genes, in particular CREBBP. This genetic architecture is similar to hyperdiploid ALL, in which the cooperation between these two genetic lesions is thought to drive relapse (26,50). In contrast CRLF2 pos DS-ALLs are characterized by high dynamics of proliferative signaling.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to previously described relapse-associated mutations and CN changes, the authors also noted enrichment of mutations in genes involved in MAP kinase signaling (8,12), including NRAS (24%), KRAS (20%), and PTPN11 (4.5%) mutations. Altogether, 48.5% of all cases had a mutation known to activate MAP kinase signaling at relapse.…”
mentioning
confidence: 96%
“…Mutations in CREBBP and P300, which encode acetyltransferases, have also been previously linked to glucocorticoid resistance in ALL (8,9). Although previously suggested to confer loss of function, continued annotation of mutations in CREBBP and P300 actually demonstrates that these mutations usually occur as heterozygous mutations at specific residues in the region encoding the enzymatic domain in each of these genes.…”
mentioning
confidence: 99%
“…Although mutations in these genes were known to occur in high hyperdiploid childhood ALL, 3,4 the frequency was higher than reported previously, partly due to a high number of KRAS mutations outside the hotspot regions in codons 12, 13, and 61. 2 Notably, in a very recent study of relapsed high hyperdiploid childhood ALL, Malinowska-Ozdowy et al 5 showed that KRAS and CREBBP mutations commonly co-occur at relapse, indicating that mutations in these genes have synergistic effects, in particular when the leukemic clones are subjected to selective pressures during chemotherapy. However, further studies are needed to delineate the exact role of the RAS signaling pathway and histone modifiers in the leukemogenesis of high hyperdiploid ALL.…”
mentioning
confidence: 99%